2002
DOI: 10.1046/j.1365-2591.2002.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic and periodontal treatments of a geminated mandibular first premolar

Abstract: The complex morphology of geminated teeth renders their endodontic and periodontal management difficult. Root canal and periodontal treatments were performed on a geminated mandibular first premolar with three canals. Clinical examination showed two separated crowns with united roots. Radiographically, two distinct pulp chambers with two joined and a third independent canal were seen. Conventional root canal treatment resulted in complete healing of the apical lesion. However, the occurrence of a vertical frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A full complement of teeth indicates gemination, whilst one tooth less than normal indicates fusion. [11] Generally geminated teeth have a single large pulp chamber and a root canal, as in the present case, Tomazinho et al . [12] in their study have reported a geminated tooth with a single large pulp chamber and a mesial and distal root canals that were joined at the apical third.…”
Section: Discussionmentioning
confidence: 65%
“…A full complement of teeth indicates gemination, whilst one tooth less than normal indicates fusion. [11] Generally geminated teeth have a single large pulp chamber and a root canal, as in the present case, Tomazinho et al . [12] in their study have reported a geminated tooth with a single large pulp chamber and a mesial and distal root canals that were joined at the apical third.…”
Section: Discussionmentioning
confidence: 65%
“…Aryanpour et al [84] reported root canal and periodontal treatment of a geminated mandibular first premolar, that is, two distinct crowns with united roots, with three canals. Kusaik et al [91] reported the root morphology of mandibular premolars in female Polish patients with Turners syndrome, based on orthopantomogram X-ray images.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen case reports that included 20 teeth have been included (12,13,17,19,(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86).…”
Section: Summary Of Case Reports Of Other Anomaliesmentioning
confidence: 99%